A case of unusual hemorrhage as a complication of dengue fever in a tertiary hospital in Dhaka - Bhuiyan, Tahmid; Das, Aditi; Rahim, Abdur; Islam, Mohammad Rafiqul (Journal of Medicine, 2024)
Common bleeding complications of dengue hemorrhagic fever are epistaxis, gum bleeding, gastrointestinal bleeding, menorrhagia, hematuria.1 Major hemorrhage like intracranial hemorrhage have been documented but rare. We present here a case of a 24 year old man with complaints of high grade intermittent fever for 5 days, upper abdominal discomfort for 3 days and swelling of right upper limb for same duration. Laboratory investigations revealed a positive dengue serology, thrombocytopenia and elevated transaminases. USG of the hand revealed a hematoma involving the right upper arm. The patient was managed conservatively with elevation and immobilization of the upper limb and recovered gradually. J MEDICINE 2024; 25: 100-101